Pengaruh Content Marketing dan Social Media Marketing Terhadap Costumer Engagement pada Generasi Z Pengguna Aplikasi Shopee di Fakultas Ekonomi Dan Bisnis Universitas HKBP Nommensen Medan - Tresia L. Naibaho; Adelina Lubis; Ihsan Effendi (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2023)
Social media is currently used as a platform for companies to introduce their products. Engagement can help companies to know their consumer behavior. This study aims to determine the effect of content marketing and social media marketing on customer engagement in Generation Z of Shopee application users at the Faculty of Economics and Business, HKBP Nommensen University, Medan. This study uses quantitative methods. This study has a population of 191 consumers using the Slovin formula, the sample used is 66 respondents. The findings in this study are content marketing (X1) has a positive and significant effect on customer engagement with a partial test, where the results obtained are T-value(3.805) Ttable (1.669) and the significance level is 0.00 0.1. For social media marketing (X2), it has a partial effect on customer engagement with T-value (3.081) T table (1.669) where the significance level is 0.003 0.1. In the coefficient of determination test, it was found that content marketing and social media marketing had an effect of 0.432 with a percentage value of 43,2% on customer engagement.